A Note on Some Identities of Frobenius-Euler Numbers and Polynomials - J. Choi; D. S. Kim; T. Kim; Y. H. Kim (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to give some identities on the Frobenius-Euler numbers and polynomials by using the fermionic p-adic q-integral equation on ℤp.